Efek Rasio Keuangan, Arus Kas Operasi, dan Ukuran Perusahaan terhadap Return Saham - Ismiati, Jihan Dwi; Hermuningsih, Sri; Maulida, Alfiatul (Universitas Proklamasi 45, 2024)
The purpose of this study is to determine the effect of operating cash flow, firm size, and financial ratios affect stock returns. The present study will employ proxies for the financial ratios, i.e. the debt-equity ratio, return on assets, total asset turnover, and current ratio. Purposive sampling was used to select 15 food and beverage companies that were listed on the IDX between 2018 and 2022 for the research sample. The financial reports of manufacturing businesses in the food and beverage subsector provided the research data. The financial reports of manufacturing businesses in the food and beverage subsector provided the research data. The data is processed using SPSS 26, and the data analysis techniques employed are classic assumption test, multiple linear regression, t-test, F-test, coefficient of determination test (R squared), and descriptive statistics. The study's findings indicate that while return on assets and total asset turnover have a positive and not significant impact on stock returns, the current ratio and debt-equity ratio have a negative and not significant effect. Stock returns are significantly impacted by operating cash flow in a positive way and by firm size in a negative way.